2010
DOI: 10.4103/0971-9784.62930
|View full text |Cite
|
Sign up to set email alerts
|

Fast-tracking in pediatric cardiac surgery - The current standing

Abstract: Fast-tracking in cardiac surgery refers to the concept of early extubation, mobilization and hospital discharge in an effort to reduce costs and perioperative morbidity. With careful patient selection, fast-tracking can be performed in many patients undergoing surgery for congenital heart disease (CHD). In order to accomplish this safely, a multidisciplinary coordinated approach is necessary. This manuscript reviews currently used anesthetic techniques, patient selection, and available information about the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 62 publications
(90 reference statements)
6
52
0
Order By: Relevance
“…Generally, the term 'early extubation' is used when the endotracheal tube is removed within 6-8 h after the surgery. However, early extubation has been associated with extubation in the operating room and as late as 24 h following surgery [14]. In our series, extubation time (maximum ventilation time 8 h) was consistent with the definition of 'early extubation'.…”
Section: Discussionsupporting
confidence: 86%
“…Generally, the term 'early extubation' is used when the endotracheal tube is removed within 6-8 h after the surgery. However, early extubation has been associated with extubation in the operating room and as late as 24 h following surgery [14]. In our series, extubation time (maximum ventilation time 8 h) was consistent with the definition of 'early extubation'.…”
Section: Discussionsupporting
confidence: 86%
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 74%
“…While certain centers adopted a fast-tracking concept and attempted extubation in the operating room or within a few hours following surgery, others still routinely continue mechanical ventilation and deep sedation postoperatively for a day or two in the intensive care unit. There is some evidence, mostly from retrospective analyses, that fast-tracking can be beneficial; however, prospective randomized studies are required to determine if fast-tracking improves outcome in children undergoing surgery for CHD (1). Several studies report on factors that prevented early extubation in children following surgery for CHD (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed kidney function as a risk indicator for adverse outcome after heart transplantation (HTX). We evaluated RIFLE-, AKIN-, and delta-creatinine-score [1] for acute kidney injury (AKI) during and immediately after HTX and its implications on patients survival. Method.…”
Section: P-35mentioning
confidence: 99%